Letter - Atholl, Katharine Marjory Stewart-Murray, Duchess of, 1874-1960
038-0033-001 NATIONAL JOINT COMMITTEE FOR SPANISH RELIEF PRESIDENT: THE DUCHESS OF ATHOLL, D.B.E., D.C.L. CHAIRMAN: MISS ELEANOR RATHBONE, M.P. VICE-CHAIRMAN: THE EARL OF LISTOWEL. HON. SECRETARIES: LADY LAYTON Mr. D.R. GRENFELL, M.P. Mr. WILFRID ROBERTS, M.P. HON. TREASURER: VISCOUNT CECIL OF CHELWOOD, P.C. K.C. ORGANISING APPEALS SECRETARY & SECRETARY BASQUE CHILDREN'S TRUST LTD.: Mrs. V.E. MILLER 39, VICTORIA STREET, LONDON, S.W.1. TELEPHONE: ABBEY 7463 8th July, 1941. Dear Friend, About a year ago, I asked your help on behalf of our Spanish Refugees, both adults and children. I am happy to tell you now that the position has in many ways changed for the better. Our many economies are bearing fruit. Work has been found for most of the adults; but, owing to the war, we have had to face a greatly reduced income for the essential work that still has to be done. Adults and children alike look to the Committee as a "home" to which they turn for help. This is needed in the periods between work (many adults are engaged on demolition in the bombed areas of London and older children on war production); others have to be transferred from one town to another; some who still suffer from wounds received in the Spanish war cannot work, and have to be maintained completely. Again, the children cannot be repatriated in wartime. Some of them are orphans, others have parents in concentration camps in France and it is impossible to get them out or to find guarantors for them. These children, therefore, have to be housed and looked after, and though many are generouusly being entertained by individual families, some hostels still have to remain. I am sure you appreciate the difficulties these times bring to us. The Committee and the refugees are deeply grateful for the help you have already generously given, but may I beg of you to continue to give them your support? The Spanish people were early victims of the menace we are now fighting, and those of them who have been helped here will, when they can finally return to Spain, carry with them a rich measure of friendship for this country. In helping them we are helping to build a happier Europe hereafter. Yours sincerely, Katharine Atholl President. The Editor, "Labour". HVT 292/946/38/33